2014
DOI: 10.1098/rspb.2014.0390
|View full text |Cite
|
Sign up to set email alerts
|

Low functional redundancy among mammalian browsers in regulating an encroaching shrub ( Solanum campylacanthum ) in African savannah

Abstract: Large herbivorous mammals play an important role in structuring African savannahs and are undergoing widespread population declines and local extinctions, with the largest species being the most vulnerable. The impact of these declines on key ecological processes hinges on the degree of functional redundancy within large-herbivore assemblages, a subject that has received little study. We experimentally quantified the effects of three browser species (elephant, impala and dik-dik) on individual-and population-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 39 publications
6
66
1
Order By: Relevance
“…African elephants (Loxodonta africana) have strong effects on woody plants due to their physical strength and height (21), causing disproportionate mortality of adult shrubs, by pulling them out (16), and trees, by pushing them over (22). Experiments with size-selective exclosures on savannas showed that elephants accounted for more than 80% of all woody plant loss across all plant height classes (22) whereas exclusion of elephants resulted in 42% more trees (23).…”
Section: Impact Of Large-herbivore Assemblages On Woody Plant Abundancementioning
confidence: 99%
See 4 more Smart Citations
“…African elephants (Loxodonta africana) have strong effects on woody plants due to their physical strength and height (21), causing disproportionate mortality of adult shrubs, by pulling them out (16), and trees, by pushing them over (22). Experiments with size-selective exclosures on savannas showed that elephants accounted for more than 80% of all woody plant loss across all plant height classes (22) whereas exclusion of elephants resulted in 42% more trees (23).…”
Section: Impact Of Large-herbivore Assemblages On Woody Plant Abundancementioning
confidence: 99%
“…Temporary reductions in herbivore numbers allow trees to regenerate and grow into taller height classes, escaping herbivory by the time herbivore populations have recovered (17). Fruit and seed consumption might offset the demographic effects of browsing injury by seed dispersal, but the net effect of large herbivore assemblages on seed predation versus dispersal remains unclear (16).…”
Section: Impact Of Large-herbivore Assemblages On Woody Plant Abundancementioning
confidence: 99%
See 3 more Smart Citations